Growth Mindset in Higher Education: Exploring Academic Buoyancy's Mediating Effect on Students' Academic Engagement and Psychological Well-being - Suharsono, Yudi; Fatimah, Siti (KnE Social Sciences, 2024)
This research investigates the effects of growth mindset and academic buoyancy on academic engagement and psychological well-being. The study involved 314 psychology students (220 females and 94 males) from a private university in Malang, Indonesia, who were selected through stratified random sampling. The research instruments utilized were the growth mindset inventory, academic buoyancy scales, Utrecht work engagement scale, and flourishing scale. Data were analyzed using structural equation modeling (SEM). The results reveal that a growth mindset significantly impacts academic engagement, psychological well-being, and academic buoyancy. Furthermore, academic buoyancy has a considerable influence on both academic engagement and psychological well-being. Importantly, academic buoyancy was identified as a significant mediator of the effects of growth mindset on academic engagement and psychological well-being. These findings have notable implications for the fields of psychology and education. However, future studies employing longitudinal or experimental approaches and incorporating diverse data sources are needed to further elucidate these relationships. Keywords: academic buoyancy, engagement, growth mindset, psychological wellbeing